Fatigue and fracture of additively manufactured polyethylene terephthalate glycol and acrylonitrile butadiene styrene polymers. (December 2022) - Kluczyński, Janusz; Szachogłuchowicz, Ireneusz; Torzewski, Janusz; Śnieżek, Lucjan; Grzelak, Krzysztof; Budzik, Grzegorz; Przeszłowski, Łukasz; Małek, Marcin; Łuszczek, Jakub
Highlights: Additively manufactured PETG samples are characterized by an increased tendency for softening in comparison to ABS counterparts. PETG samples are characterized by 35% bigger cycles to failure value than ABS counterparts, ABS samples were characterized by cracking in the whole fracture area instead of cracking particularly in each deposited material line. Abstract: This paper aims to study and compare the static tensile properties and Low Cycle Fatigue (LCF) deformation behavior of Additively Manufactured (AM) samples made of two commonly used polymers: Polyethylene Terephthalate Glycol (PET-G) and Acrylonitrile Butadiene Styrene (ABS). Such materials are commonly in use in the Material Extrusion (ME) AM technologies – especially in Fused Deposition Modelling (FDM) or Fused Filament Fabrication (FFF). That kind of approach would be useful to understand the fracture phenomena of AM parts obtained by means of FDM/FFF technologies which are entirely different than in the conventionally made material, because of the characteristic layered structure of AM parts. The study has been supplemented by additional fracture analysis of AM samples subjected to LCF tests. The conducted research exposed an increased LCF of PET-G samples (36050 cycles at constant strain equal to ε = 0.40%) in comparison to ABS (24586 cycles at the same strain level). At the same time, PET-G samples indicated a significant material softening during LCF testing. Such a phenomenon was better described by additional analysis with the use of the Morrow equation which indicated quasi-brittle cracking with visible brittle fracture phenomena in PET-G samples.